Cognitive curiosity and its relationship to academic flexibility among students of the children's sports department (Journal of the College of Basic Education, 2024)
The current research aims to find out 1- Cognitive curiosity among female students in the kindergarten department2- Academic flexibility among female students in the kindergarten department3- The correlation between cognitive curiosity and academic flexibility among female students in the kindergarten department The researcher adopted the Cognitive Curiosity Scale and the Academic Flexibility Scale, and conducted validity and reliability for them. She applied the two scales to the basic research sample of (400) female students from the kindergarten department. Then, she processed the data using (SPSS) and used statistical methods, which are the one-pair t-test and the Pearson correlation coefficient, and arrived at Search results for: The kindergarten students are have cognitively curious.The kindergarten students have academic flexibility.There is a positive relationship between cognitive curiosity and academic flexibility among female students in the kindergarten department. The current research aims to find out:The kindergarten The kindergarten The kindergarten